Silage characteristics and acceptability of maize stover, cassava tops ensiled with Albizia saman pods (2015)
The use of preserved feedstuff in form of silage is a very good strategy to improve livestock performance during seasonal shortages. This study was conducted to determine the silage characteristics and the co efficient of preference of the experimental diets containing different portions of Cassava tops (CST), Maize Stover (MST) ensiled with Albizia saman pods (ASP). The ensiled mixtures were: T1: 40% CST + 0% ASP + 60% MST, T2: 30% CST + 10% ASP+ 60% MST, T3: 20% CST + 20% ASP + 60% MST, T4: 10% CST + 30% ASP + 60%, MST and T5: 0% CST + 40% ASP + 60% MST. The pH of silage ranged between 4.26 and 4.44, temperature ranges between 27.74 and 31.62°C, odour of silage were fruity. The acceptability studies using ruminants indicated that the silages had high coefficient of preference and nutritive value. This study showed that silage mixture containing cassava tops, Albizia saman pods and maize stover could be a better alternative feedstuff for ruminants during the dry season.